Effect of Ticagrerol versus Clopidogrel on Inflammatory Bio-marker in Patients with Chronic Stable Angina Patients after Percutaneous Coronary Intervention (University Heart Journal, 2016)
Background: Ischemic heart disease remains the leading cause of death in both developed and under developed countries. The use of antiplatelet drugs specifically the thienopyridine has become a standard for the treatment of acute coronary syndrome. These drugs irreversibly inhibit the platelet aggregation by blocking the P2Y12 receptor. But currently this therapeutic choice has become limited due to potential interaction with other drugs, slow hepatic conversion, genetic resistance and narrow therapeutic safety margin. Ticagrerol, a reversible P2Y12 receptor inhibitor may represent a significant advancement over currently available oral antiplatelet drugs.Objectives: The study was intended to compare the effect of Ticagrelor and Clopidogrel on inflammatory and oxidative stress markers in patients of chronic stable angina (CSA) following percutaneous coronary intervention (PCI).Materials & Methods: The present prospective observational study was carried out in the Department of Pharmacology, Cardiology and Microbiology, BSMMU, Dhaka from September 2014 to February 2016. The study included a total of 100 CSA patients. Patients were divided into two groups, Ticagrelor and Clopidogrel treated groups (each having 50 patients). The baseline laboratory parameters- High sensitive C-reactive protein (hs-CRP), bleeding time, clotting time, were measured and then patients of both groups underwent PCI. The same parameters were again assessed at follow up after 4 weeks of intervention. Total 12 patients from Ticagrelor and 14 patients from Clopidogrel groups were dropped out. Comparisons of the laboratory parameters were made between two groups at baseline and at follow up and also within group before and after intervention. Result: In the present study at baseline characteristics of patients treated with Ticagrelor and Clopidogrel were almost identical in terms of age, sex, diabetes and hypertension. The inflammatory marker hs-CRP was also similar in both groups at baseline. At follow up hs-CRP was significantly reduced from baseline 19.7 mg/dl to 1.7 mg/dl (p value- 0.001) in ticagrerol group and 18.4 mg/dl to 2 mg/dl (p value-0.001) in clopidogrel group. There was no significant change in bleeding time and clotting time in both groups of patients.Conclusion: The study concluded that both Ticagrelor and Clopidogrel are similar in improving the status of the inflammatory marker, resulting from inflammatory processes in patients of chronic stable angina.University Heart Journal Vol. 11, No. 1, January 2015; 42-44